2009
DOI: 10.1111/j.1537-2995.2009.02211.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between duration of storage of transfused red blood cells and morbidity and mortality in adult patients: myth or reality?

Abstract: From the currently available published data, it is difficult to determine whether there is a relationship between the age of transfused RBCs and outcome in adult patients, except possibly in trauma patients receiving massive transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
150
1
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 45 publications
3
150
1
9
Order By: Relevance
“…This is especially true for certain categories of recipients, such as traumatized, post-operative and critically ill patients. 1 Despite accumulating retrospective evidence of reduced blood viability after the first 2 weeks of storage, 2 definitive results from prospective, randomized, double-blind clinical trials are still lacking 3,4 or inconclusive. These problems are mainly due to the intrinsic statistical limitations of the experimental models 4 or the lack of common methods and shared standards between laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for certain categories of recipients, such as traumatized, post-operative and critically ill patients. 1 Despite accumulating retrospective evidence of reduced blood viability after the first 2 weeks of storage, 2 definitive results from prospective, randomized, double-blind clinical trials are still lacking 3,4 or inconclusive. These problems are mainly due to the intrinsic statistical limitations of the experimental models 4 or the lack of common methods and shared standards between laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…In noncardiac patients, such as cases of elective colorectal cancer surgery, two studies 30,31 with different design investigated the effects of RBC storage on postoperative infections generating conflicting results. 5 In the first study, infections occurred more frequently in patients receiving old blood (stored for more than 21 days) when compared to fresh blood (stored for <21 days; 46% vs. 32%). 30 Nevertheless, the same authors showed in a second study that infection rates were similar in patients transfused with old blood (stored > 21 days) and fresh blood (stored for < 21 days; 34% vs. 29%).…”
mentioning
confidence: 99%
“…3 Although the biochemical effects of storage on RBCs are well documented, the clinical consequences of receiving RBCs of longer storage duration are currently a matter of debate. 5 Three recent randomized clinical trials did not find significant differences between fresh and old blood in patients undergoing cardiac surgery 6 or admitted to the intensive care unit (ICU) 7 and in hospitalized patients. 8 Immunosuppression induced by surgery and anesthesia may be aggravated by transfusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] To our knowledge, no systematic review currently exists that exclusively examines the impact of the age of transfused RBCs on mortality in the trauma patient population, although other patient populations have been investigated. [19][20][21][22][23][24] The objective of this review was to assess the available evidence for the impact of the age of stored RBCs given as transfusions in the trauma population on patient mortality.…”
mentioning
confidence: 99%